Penerapan Reward dan Punishment dalam Meningkatkan Motivasi Belajar Siswa - Yuliana; Faizatul Ummya (JURNAL AS-SAID, 2023)
This study aims to find out how the implementation of reward and punishment increases students’ motivation with the class VIII E of Integral Islamic Middle School Luqman Al-Hakim Batam. The sample of this study was the students of class VIII E SMP Islam Integral Luqman Al-Hakim Bata. The type of this study is qualitative research.The results of this study were implemented at Integral Islamic Middle School Luqman Al-Hakim Batam. Reward and punishment was aimed as an effort to increase students’ motivation.This study concluded the reward and punishment that were implemented have succeeded in having a positive impact on increasing the students’ learning motivation.